Study on Effect of Interlayer in Friction Welding for Dissimilar Steels: SS 304 and AISI 1040. (2016) - James, Jeswin Alphy; Sudhish, R.
Abstract: Friction welding is a common type of welding technique now a day. The study of efficiency of friction welded joints of different materials is seems to be very relevant. This paper discussed the properties of friction welded joint of austenitic stainless steel 304 and medium carbon steel AISI 1040 and compared the properties of weld with and without interlayer at different welding parameters. The interlayer materials selected for the study is nickel. The experiments were conducted with the welding parameters such as forging pressure, rotational speed and friction time. The parameters are optimized by choosing three input parameters and three input level. Taguchi Orthogonal array is used for designing the experiment. Finally microstructure, tensile strength, micro hardness and FESEM-EDS results are compared and analysed for weld with nickel interlayer and without interlayer to study the effect